2011
DOI: 10.1002/cbf.1784
|View full text |Cite
|
Sign up to set email alerts
|

Influence of estrogen on pulmonary arterial hypertension: role of oxidative stress

Abstract: Pulmonary arterial hypertension (PAH) is a disease that increases the pulmonary vascular resistance, causing hypertrophy and subsequent right heart failure. Oxidative stress is involved in the pathogenesis of PAH, and estrogen is considered an antioxidant. Thus, the aim of this study was to test the hypothesis that estrogen could attenuate PAH by modulating oxidative stress. Female Wistar rats were ovariectomized or suffered the surgery simulation (sham). After 7 days, subcutaneous pellets with 17β-estradiol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Perhaps, over a longer period, a more prominent increase could be observed, as reported by Konskenvuo et al (2010). This increase in pulmonary pressure seems to be insufficient to induce RV hypertrophy, as was demonstrated in this study, which corroborates previous data from our laboratory (Siqueira et al 2011). This outcome differed from that observed in male rats, where an evident RV hypertrophy was documented (Colombo et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps, over a longer period, a more prominent increase could be observed, as reported by Konskenvuo et al (2010). This increase in pulmonary pressure seems to be insufficient to induce RV hypertrophy, as was demonstrated in this study, which corroborates previous data from our laboratory (Siqueira et al 2011). This outcome differed from that observed in male rats, where an evident RV hypertrophy was documented (Colombo et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…38,39 In a study, estrogen levels may help to avoid the appearance of pulmonary edema, the characteristic of MCT model and right ventricular failure. 40 Based on these results, it can be considered that the gender difference found in MCT-induced pulmonary hypertension resulted from higher estrogen levels in female rats than in males.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a growing body of studies has demonstrated that estrogen can act as an antioxidant to regulate cardiovascular function. 3437 In a spontaneous hypertensive rat model, ovariectomy increased ROS excretion in females, suggesting that estrogen suppresses levels of ROS. 38 In contrast to our previous findings that perinatal nicotine enhances vascular NADPH oxidase (Nox2) protein expression in male adult offspring, 28 current findings that nicotine had no effect on Nox2 expression in female offspring, suggest a sex difference in nicotine-induced programming of ROS-related gene expression.…”
Section: Discussionmentioning
confidence: 99%